Proses Pembelajaran Pembuatan Laporan Keuangan pada Siswa-Siswi SMA Sederajat - Mulyani Rizki (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Good financial management is an important skill that needs to be taught early on. The learning process of financial reporting at the high school level aims to provide students with a basic understanding of accounting principles and the ability to prepare financial reports. This activity is part of a community service program designed to improve financial literacy and prepare the younger generation to face future economic challenges. The method used involves a practical approach with the delivery of basic theory, case-based training, and evaluation of learning outcomes. The results of the activity showed an increase in students' understanding of financial reporting concepts, such as balance sheets, income statements, and cash flows. Further discussion highlighted the importance of integrating this material into the school curriculum so that students are better prepared to face the world of work and independent businesses.